2021
DOI: 10.2478/sg-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide bioinformatics analysis revealed putative substrate specificities of SABATH and MES family members in silver birch (Betula pendula)

Abstract: Plant SABATH family members catalyze the methylation of many hormones, signaling molecules, and floral scent metabolites, including salicylic acid (SA), jasmonic acid (JA), and indol-3 acetic acid (IAA). Demethylation of resulting methyl esters was executed by members of the MES family. Members of both families are significantly involved in plant developmental processes. Here, using different bioinformatics tools, we studied the evolutionary relationship and characterized the putative functions of the family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The inherent stability of this structure ensures that plants can maintain various biological functions in the face of diverse environmental conditions and physiological requirements. Homologs of MES genes harboring the conserved catalytic triad have been identified in potato, grape, peach, tomato, poplar, birch, and numerous other plant species. ,,,,, Certain MES members participate in the metabolism and signal transduction of different hormones, thereby regulating plant growth and development. In peach, most of the MES genes were also found to exhibit high expression in fruits tissues, while poplar PtSABP2 and Arabidopsis AtMES17 were predominantly expressed in roots. , The results of this research suggest that the FvMES gene family members display varied expression patterns throughout different stages of development and in various tissues of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent stability of this structure ensures that plants can maintain various biological functions in the face of diverse environmental conditions and physiological requirements. Homologs of MES genes harboring the conserved catalytic triad have been identified in potato, grape, peach, tomato, poplar, birch, and numerous other plant species. ,,,,, Certain MES members participate in the metabolism and signal transduction of different hormones, thereby regulating plant growth and development. In peach, most of the MES genes were also found to exhibit high expression in fruits tissues, while poplar PtSABP2 and Arabidopsis AtMES17 were predominantly expressed in roots. , The results of this research suggest that the FvMES gene family members display varied expression patterns throughout different stages of development and in various tissues of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive genomic analysis revealed that SAMT and SABP2 enzymes belong to the SABATH and MES families, respectively (D'Auria et al 2003;Yang et al 2008). Both families were recently studied in silver birch (Betula pendula) (Singewar et al 2021). Plant SABATH and MES family members catalyze methylation and demethylation of many hormones, signaling molecules, and floral scent metabolites, including SA, JA, and IAA.…”
Section: Candidate Genes Of Mesa Biosynthesis and Metabolism In Lowand High-mesa-producing Birchesmentioning
confidence: 99%